2019
DOI: 10.1002/1873-3468.13379
|View full text |Cite
|
Sign up to set email alerts
|

Axonemal doublet microtubules can split into two complete singlets in human sperm flagellum tips

Abstract: Motile flagella are crucial for human fertility and embryonic development. The distal tip of the flagellum is where growth and intra‐flagellar transport are coordinated. In most model organisms, but not all, the distal tip includes a ‘singlet region’, where axonemal doublet microtubules (dMT) terminate and only complete A‐tubules extend as singlet microtubules (sMT) to the tip. How a human flagellar tip is structured is unknown. Here, the flagellar tip structure of human spermatozoa was investigated by cryo‐el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…We found that doublets can transition into singlets by two possible arrangements, either by a doublet splitting into two independent singlets ( Fig 7D-F, left panels) or by the B-tubule terminating abruptly ( Fig 7D-F, right panels). Similar patterns have been observed in human sperm (Zabeo et al, 2019).…”
Section: Singlet Microtubules In the Endpiece Are Capped By A Conservsupporting
confidence: 86%
“…We found that doublets can transition into singlets by two possible arrangements, either by a doublet splitting into two independent singlets ( Fig 7D-F, left panels) or by the B-tubule terminating abruptly ( Fig 7D-F, right panels). Similar patterns have been observed in human sperm (Zabeo et al, 2019).…”
Section: Singlet Microtubules In the Endpiece Are Capped By A Conservsupporting
confidence: 86%
“…(iii) the principal piece of the flagellum, typically 40-60 µm in length (although much longer in some species [8]), the core of which is the 9+2 axoneme that produces and propagates active bending waves through dynein-ATPase activity [9]; and (iv) the end piece, typically a few microns in length, which consists of disorganized singlet microtubules (sMTs) only [10].…”
Section: Introductionmentioning
confidence: 99%
“…In CEM cilia, the proximal region following the transition zone has nine doublet MTs lacking Y links; these doublet MTs splay to form individual 13 protofilament A‐tubule and 10 protofilament B‐tubule singlet MTs which rejoin in the sub‐distal region to form “modified doublets” with A and B tubules (where both tubules are complete) (Silva et al., 2017) (Figure 5b). The splitting of doublet MTs into A‐tubule and B‐tubule singlets is also observed in mammalian sperm flagella, indicating that this CEM ultrastructural specialization is evolutionarily conserved (Afzelius et al., 1995; Zabeo et al., 2019).…”
Section: Evn Cilia Have Distinct Axonemal Features That Are Sculpted By the Tubulin Codementioning
confidence: 96%